Pharmacokinetics of Alemtuzumab in Pediatric Patients Undergoing ex vivo T-Cell Depleted Haploidentical Hematopoietic Cell Transplantation - Bhoopalan, Senthil Velan (Cancer Chemother Pharmacol, 2020)
PURPOSE: Alemtuzumab is a humanized monoclonal antibody against CD52 which is predominantly present on T- and B-lymphocytes. Alemtuzumab has been used as part of conditioning regimens for prophylaxis against rejection and GVHD. While the mechanism of action is well-understood, the pharmacokinetics of this drug in children needed to be studied in more detail especially in the setting of ex vivo T-cell depleted hematopoietic cell transplantation (HCT). METHODS: Serum alemtuzumab levels were measured at various time points in 13 patients who underwent haploidentical HCT utilizing ex vivo donor T-cell depletion. Alemtuzumab was administered subcutaneously at a cumulative dose of 45 mg/m(2) from days −13 to −11. A one-compartmental model was used to fit the data using non-linear mixed effects modeling. RESULTS: We determined the median half-life to be 11 days. Alemtuzumab clearance increased with increasing baseline lymphocyte count (p = 0.008). Additionally, clearance increased with weight and age (p ≤ 0.035). AUC of alemtuzumab did not have any significant relationship with type of leukemia, overall survival, engraftment, immune reconstitution, mixed chimerism or GVHD, although the number of subjects in this pilot study was limited. CONCLUSION: Absolute lymphocyte count and body weight affect alemtuzumab clearance. We also demonstrate feasibility of body surface area-based dosing of alemtuzumab in pediatric HCT patients. Further studies are needed to evaluate the role of monitoring alemtuzumab serum concentrations to balance the prevention of graft rejection and GVHD with the promotion of rapid donor immune reconstitution.